Turn-On type fluorescent polymer, synthesis method thereof and application of Turn-On type fluorescent polymer in uranyl ion detection
The "Turn-On" type fluorescent polymer synthesized at room temperature solves the problem that uranyl ion detection requires a high temperature and high pressure environment in the prior art, and achieves rapid, sensitive and highly selective detection of uranyl ions, which is suitable for industrial scale production and practical applications.
Patent Information
- Application Number
- CN202411630896.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art has high temperature, high pressure, and anaerobic environment requirements in the detection of uranyl ion, and the fluorescent probe type is mainly "Turn-off" type, which limits the widespread application of materials.
A room temperature synthesized "Turn-On" fluorescent polymer was developed, using tetraphenylethylenetetradeld and 3,3-dihydroxybiphenyldiamine as main components, and synthesized at room temperature, and achieved high sensitivity detection of uranyl ions through a specific combination of solvents and catalysts.
It realizes rapid, sensitive and highly selective detection of uranyl ions, reduces energy consumption, is suitable for industrial large-scale production, and shows good anti-interference ability and detection accuracy in practical applications.
Smart Images

Figure CN119505134A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental detection, and in particular relates to a Turn-On fluorescent polymer and a synthesis method thereof and an application thereof in detecting uranyl ions. Background Art
[0002] Energy, as the foundation of human life and development, is crucial in promoting global economic and environmental development. However, with the shortage of fossil energy and the increasingly severe prevention and control of environmental pollution, traditional fossil energy can no longer fully meet the needs of the rapidly developing modern economy. Therefore, it is urgent to pursue new energy sources that can both promote economic development and reduce carbon emissions. Among them, nuclear energy, as a carbon-free energy, can generate zero-emission electricity and is the best choice for the corresponding energy structure transformation.
[0003] With the rapid development of the nuclear energy industry, the discharge of nuclear wastewater has aroused great concern and strong panic around the world because of its serious radiation hazards to the ecological environment. Among them, uranium, as an important radioactive nuclide, plays an irreplaceable role in nuclear fission and nuclear weapons. However, once unregulated uranium migrates into the environment, its potential radioactivity and chemical toxicity may cause various irreversible damages to human health, such as cell damage, kidney disease, osteosarcoma and liver disease, and even cause death. Obviously, in order to ensure radiation protection and nuclear safety, timely warning of uranium contamination in environmental samples is necessary.
[0004] Therefore, in order to meet the needs of uranium contamination warning in emergency situations, it is highly desirable and necessary to adopt sensitive and rapid uranium visual detection strategies in the field instead of complex laboratory detection methods such as inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma atomic emission spectrometry (ICP-AES) and surface enhanced Raman spectroscopy (SERS). Fluorescence methods such as semiconductor quantum dots (QDs), metal organic frameworks (MOFs), and covalent organic frameworks (COFs) have the advantages of low cost, high efficiency, and ease of use, especially in terms of naked eye detection, and have been used for rapid uranium detection. However, semiconductor quantum dots (QDs) and metal organic frameworks (MOFs) require metal ions as nodes, which are toxic, and the preparation and modification steps are complicated, and the selectivity is not ideal, which will hinder the widespread application of these methods. Covalent organic frameworks (COFs) are a class of crystalline porous polymers with adjustable porosity and large specific surface area, which provide convenient conditions for the extraction and detection of radionuclides. However, the synthesis of COFs often requires an oxygen-free, high-temperature environment, and the reaction conditions are highly dependent on the reactivity, solubility, and degree of reaction of the organic building monomers, which makes it difficult to obtain excellent crystalline COFs. Porous organic polymers (POPs) are organic porous materials with microporous or mesoporous structures, mainly composed of covalently linked light elements such as C, H, O, and N. Porous organic polymers have the characteristics of low skeleton density, adjustable pores, large specific surface area, and good physicochemical stability. Therefore, they can play a good role with guest molecules through non-covalent interactions, which has enabled POPs to develop rapidly in the fields of gas separation, storage, pollutant removal, and sensing. Compared with traditional small molecule sensors, POPs materials are insoluble in water and most organic solvents, which is conducive to their separation, regeneration, and reuse. In addition, the porous nature of porous organic polymers can provide a rich microenvironment for guest molecules to interact, and the amorphous porous organic polymers have low crystallinity and weaken the non-radiative transition caused by the π-π stacking interaction between molecular layers, which is conducive to the production of excellent fluorescence properties. At present, porous organic polymer materials have attracted the interest of many scientific researchers, and various sensors for uranyl ions have been built based on mechanisms such as photoinduced electron transfer (PET) and fluorescence resonance energy transfer (FRET). However, since most porous organic polymer materials require high temperature, high pressure, and oxygen-free environments, and are basically "turn-off" type fluorescent probes, this limits the practical application of porous organic polymer materials.Therefore, it is necessary to develop a "Turn-On" fluorescent polymer that can be synthesized at room temperature for the detection of uranyl ions. Summary of the invention
[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present invention proposes a Turn-On fluorescent polymer having a fluorescence enhancement response to uranyl ions, and the fluorescent polymer can be synthesized at room temperature, and is more suitable for industrial-scale production and application.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a Turn-On fluorescent polymer, wherein the fluorescent polymer has the structure shown below:
[0008]
[0009] The second aspect of the present invention provides a method for preparing the Turn-On fluorescent polymer described in the first aspect, specifically: tetraphenylethylenetetraaldehyde and 3,3-dihydroxybenzenediamine are mixed, and then 1,4-dioxane, benzyl alcohol, mesitylene and acetic acid solution are added, and after sufficient dissolution, the mixture is degassed and sealed under vacuum, and then allowed to stand in a greenhouse for more than 3 days, and finally a yellow solid product is collected.
[0010] Preferably, the molar ratio of tetraphenylethylenetetraaldehyde to 3,3-dihydroxybenzenediamine is 1:1-3.
[0011] Preferably, the concentration of the acetic acid solution is 5-7M.
[0012] Preferably, the volume ratio of the 1,4-dioxane, benzyl alcohol, mesitylene and acetic acid solution is 700-900:700-900:1315-1355:150-250.
[0013] Preferably, degassing under vacuum is performed by rapid freezing in a liquid nitrogen bath and then degassing by freeze-pump-thaw cycles.
[0014] Preferably, collecting the yellow solid product comprises: filtering the yellow solid product, washing it with tetrahydrofuran and ethanol respectively, filtering and collecting the yellow solid, and drying it.
[0015] The third aspect of the present invention provides the use of the Turn-On fluorescent polymer described in the first aspect in detecting uranyl ions.
[0016] Preferably, the method for detecting uranyl ions is as follows: the Turn-On type fluorescent polymer described in the first aspect is dispersed in a solvent to prepare a 0.01-0.05 mg / mL stock solution, and then a uranyl ion (UO2)-containing solution is added to the stock solution at a volume ratio of 8-10:1. 2+ ) was allowed to stand for more than 30 min, and then the fluorescence emission spectrum was measured at an excitation wavelength of 314 nm. Finally, the uranyl ion concentration of the test solution was obtained based on the linear response curve between the fluorescence intensity at 401 nm and the uranyl ion concentration.
[0017] More preferably, the solvent is a mixed solvent of dimethylacetamide (DMAC) / H2O=9:1.
[0018] More preferably, the stock solution further contains EDTA. 3+ and Cu 2+ It will strongly interfere with the fluorescence intensity of TPE-COPs to uranyl ions, while EDTA can 3+ and Cu 2+ Masking, thus not interfering with TPE-COPs on UO2 2+ Response.
[0019] More preferably, the detection limit of uranyl ions is 30.6 nM.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention cleverly utilizes the structural characteristics of tetraphenylethylenetetraaldehyde to synthesize an organic porous polymer with fluorescence enhanced response to uranyl ions at room temperature, which not only expands the detection method of uranyl ions, but also reduces energy consumption in synthesis, enriching UO2 2+ In general, the present invention has the following advantages:
[0022] (1) The fluorescent polymer TPE-COPs synthesized in the present invention is a "Turn-On" fluorescent polymer, which has the advantages of high sensitivity, high selectivity and rapid response in detecting uranyl ions. It can simultaneously improve the sensitivity and anti-interference ability, and achieve a comprehensive balance of detection limit, detection range and selectivity. It can be used to detect trace uranyl ions, and shows great application potential and value in biomedical research and rapid visualization detection of environmental samples.
[0023] (2) The synthesis of the fluorescent polymer TPE-COPs of the present invention can be completed at room temperature, the process is simple, and no harsh environment such as high temperature, high pressure, and oxygen-free is required, which is more suitable for industrial-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The synthetic route of TPE-COPs;
[0025] Figure 2 is the PXRD spectrum of TPE-COPs (the thumbnail is a partial enlarged view of the PXRD spectrum of TPE-COPs);
[0026] Figure 3 The fluorescence intensity of TPE-COP and UO2 2+ Concentration relationship diagram;
[0027] Figure 4 The excitation and emission spectra of TPE-COPs in DMAC solution (a) and the excitation and emission spectra of TPE-COPs in DMAC / H2O solution (b);
[0028] Figure 5 The effects of TPE-COPs on UO2 in different solvents 2+ The fluorescence response diagram of (a) and the fluorescence intensity change when the water content in the mixed solvent DMAC / H2O ranges from 90% to 10% (b);
[0029] Figure 6 pH to UO2 2+ The effect of fluorescence enhancement signal;
[0030] Figure 7 The contact time to UO2 2+ The effect of fluorescence enhancement signal;
[0031] Figure 8 For TPE-COPs and UO2 2+ The fluorescence stability of the effect;
[0032] Fig. 9 The effects of anions (a) and metal cations (b) on the response signals of TPE-COPs;
[0033] Fig.10 The effects of TPE-COPs on UO2 under the interference of metal cations (500 μM) (a) and anions (500 μM) (b) 2+ (5 μM) response changes;
[0034] Fig.11 Fe 3+ (a) and Cu 2+ (b) Response of TPE-COPs to UO2 2+ Interference and masking of fluorescence signals;
[0035] Fig.12 For TPE-COPs at different concentrations of UO2 2+Emission spectra (a) and fluorescence intensity of TPE-COPs in the presence of UO2 2+ (b) Linear fitting curve of the concentration. DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0037] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0038] Example 1: Synthesis of covalent organic polymers (TPE-COPs)
[0039] 1. Add tetraphenylethylenetetraaldehyde (17.8 mg, 40 μmol) and 3,3-dihydroxybenzenediamine (17.3 mg, 80 μmol) into a 10 mL heat-resistant glass tube, and then add 1,4-dioxane (800 μL), benzyl alcohol (800 μL), mesitylene (1335 μL) and acetic acid (AcOH) solution (200 μL, 6 M) to the mixture. After the mixture is ultrasonically dissolved, the glass tube is quickly frozen in a liquid nitrogen bath, and the glass tube is degassed and sealed through three freeze-vacuum-thaw cycles (the glass tube is quickly frozen in a liquid nitrogen bath, and then degassed with a vacuum pump, and the above operation is repeated three times after dissolution), and then placed in a safe location in a greenhouse for 3 days. After the yellow target appears, the yellow solid is filtered and washed three times with tetrahydrofuran (THF 3×20mL) and anhydrous ethanol (3×20mL), and finally the yellow solid is collected by filtration and placed at 70°C for vacuum drying for 12 hours to prepare TPE-COPs. The specific preparation process is as follows Figure 1 shown.
[0040] The crystalline structure of TPE-COPs was detected by X-ray powder diffraction (PXRD). Figure 2 red line) and 3,3-dihydroxybenzenediamine ( Figure 2 The blue line) has a typical crystal structure. TPE-COPs ( Figure 2 The black line) shows a strong broad peak at 20-30°, and the surface TPE-COPs has an amorphous structure, indicating that the material is an amorphous polymer.
[0041] 2. Considering that the polarity of the solvent, the concentration of the catalyst, and the reaction time will have a certain impact on the performance of COPs, this experiment used different solvents and catalysts to synthesize the same COPs and explored its performance, as shown in Table 1. The specific synthesis method is as follows:
[0042] Take several 15mL centrifuge tubes, add tetraaldehyde tetraphenylethylene (17.8mg, 40μmol) and 3,3-dihydroxybenzenediamine (17.3mg, 80μmol), add about 3mL of different solvents and catalysts to each centrifuge tube, and then add 0.3mL (6M or 12M) of HAC. After the mixture is ultrasonically mixed, the glass tube is quickly frozen in a liquid nitrogen bath, and the glass tube is degassed and sealed through three freeze-vacuum-thaw cycles, and left at room temperature for 3 or 5 days. After the yellow target appears, filter the yellow solid, wash it three times with tetrahydrofuran (THF 3×20mL) and anhydrous ethanol (3×20mL), and finally filter and collect the yellow solid, and place it under vacuum at 70℃ for 12h.
[0043] Depend on Figure 3 It can be seen that TPE-COPs has a significant effect on UO2 2+ The TPE-COPs synthesized under the conditions of 1,4-dioxane (800 μL), benzyl alcohol (800 μL), mesitylene (1335 μL) and acetic acid solution (200 μL, 6 M) showed high sensitivity to UO2 2+ There is a good linear relationship (the detection method of TPE-COPs for uranyl ions is specifically referred to Example 2), and the minimum detection limit is 0.0306 μΜ (7.283 ng / L). Therefore, the COPs synthesized under this condition were subsequently used for performance exploration.
[0044] Table 1 Conditions for synthesizing TPE-COPs
[0045]
[0046]
[0047] Example 2: TPE-COPs for the detection of uranyl ions and optimization of detection conditions
[0048] 1. Optimal fluorescence emission spectrum of TPE-COP
[0049] Take 5 mg of TPE-COPs and disperse it in 200 mL of N,N-dimethylacetamide to prepare a 0.025 mg / mL TPE-COPs stock solution. Then take several 1.5 mL centrifuge tubes, add 1000 μL of the stock solution to one group, add 900 μL of the stock solution to another group, and add 100 μL of 50 μM uranyl ion to each group, let it stand for 30 minutes, and shake it well. Figure 4 It can be seen that the emission peak of pure TPE-COPs is at 384 nm. 2+ Later, the emission peak will red-shift to 401nm, and the corresponding excitation wavelength is 314nm, so subsequent measurements are made at an excitation wavelength of 314nm.
[0050] 2. Solvent Optimization
[0051] In order to explore the fluorescence intensity of TPE-COPs in different solvents, this experiment selected the commonly used laboratory solvents ethanol, tetrahydrofuran, dimethylacetamide (DMAC) and DMAC / H2O mixed solvents with a volume fraction of H2O (fw water) between 90% and 10% as the solvents of the fluorescent sensor. The fluorescence intensity of TPE-COPs solution (0.025 mg / mL) itself and the addition of 5 μM UO2 2+ The fluorescence intensity changes after Figure 5 a It can be seen that the fluorescence intensity of COPs dispersed in different solvents is significantly different. The fluorescence intensity of COPs is the strongest when dispersed in DMAC / H2O=9:1. COPs have almost no fluorescence when dispersed in water, and there is no change in fluorescence intensity after adding uranyl ions. This may be because COPs are too hydrophobic. After adding DMAC, COPs can be well dispersed in the mixed solution of DMAC and water, and the polarity of the solution becomes smaller, and the fluorescence intensity becomes stronger. And from Figure 5 As can be seen in b, the smaller the proportion of water in the mixture, the greater the fluorescence intensity. This may be because the hydrogen bonding between molecules will weaken as the water content decreases. Therefore, the fluorescence intensity of COPs is the strongest when DMAC / H2O=9:1, so subsequent experiments were carried out under this condition.
[0052] 3. pH
[0053] In aqueous solution, the protonation degree of the binding site between the material and the guest molecule will be affected by the pH of the solution. In order to explore the effect of the pH of the mixed solvent (v / v, DMAC / H2O) on TPE-COPs, two sets of comparative experiments were designed. One set used 0.1M Tris-HCl as a buffer solution to prepare uranium solutions (100μL 50μM) with pH values of 1, 2, 3, 4, 5, 6, 7, 8, and 9. The other set used aqueous solutions with pH values of 1, 2, 3, 4, 5, 6, 7, 8, and 9 mixed with DMAC to obtain background solutions. The results were used to explore the effect of the pH of the mixed solvent (v / v, DMAC / H2O) on the protonation degree of the binding site between the material and the guest molecule. 2+ Considering that the solution pH is a key factor in determining the existence of uranium in the solution and the detection ability, the optimal pH in the range of pH = 1 to 10 is sought to obtain the best response performance to uranium. Figure 6 It can be seen that the material's detection performance for uranium has a strong pH dependence. When the pH is between 3-5, the fluorescence enhancement effect caused by uranium is most obvious.
[0054] 4. Optimal contact time
[0055] like Figure 7 As shown, TPE-COPs (0.025 mg / mL) and UO2 2+ The response can reach equilibrium within 30 min. 2+ When the concentration is low, the fluorescence intensity is 2.6 times higher than the blank within 1 minute. After reaching equilibrium in 30 minutes, the fluorescence intensity is 13 times higher than the blank. Therefore, the purpose of rapid detection of environmentally polluted water bodies can be achieved.
[0056] 5. Study on fluorescence stability
[0057] Take 5 mg of TPE-COPs and disperse them in 200 mL of DMAC to prepare a 0.025 mg / mL TPE-COPs stock solution. Then take 900 μL of TPE-COPs stock solution in a 1.5 mL centrifuge tube and add 100 μL of 50 μM UO2 2+ , and then use FL-2700 fluorescence spectrometer to detect its fluorescence changes. Figure 8 It can be seen that TPE-COPs has good fluorescence stability, and the fluorescence intensity has no obvious change within two hours, which can be used for subsequent TPE-COPs detection of UO2 2+ Provide favorable conditions.
[0058] 6. Selectivity
[0059] Take 5 mg of TPE-COPs and disperse them in 200 mL of DMAC to prepare a 0.025 mg / mL TPE-COPs stock solution. Then take several 1.5 mL centrifuge tubes, add 900 μL of the stock solution, and then add 100 μL of different metal ions (UO2 2+ 、Ni + 、Co 2+ , Pb 2+ 、Zn 2+ , Cu 2+ 、Na + Mg 2+ , Tb 3+ 、Eu 3+ , Fe 3+ 、Co 2+ , K + , Ca 2+ Mg 2+ 、Ag + , Cs + ), except UO2 2 + The concentration of the other metal ions is 500 μM, except for the concentration of 50 μM. The metal ion solution is prepared by the corresponding nitrate, and the anion solution is prepared by the corresponding sodium salt. At the same time, a sample without adding any metal ions is prepared as a blank sample. After thorough mixing, the fluorescence emission spectrum of the solution is measured using FL-2700. Fig. 9 It can be seen that TPE-COPs has a significant effect on UO2 2+ Has good selectivity.
[0060] 7. Anti-interference
[0061] (1) Metal ions
[0062] Take 5 mg of TPE-COPs and disperse them in 200 mL of DMAC to prepare a 0.025 mg / mL TPE-COPs stock solution. Then take several 1.5 mL centrifuge tubes, add 900 μL of TPE-COPs stock solution, and then add 100 μL of ionic solution (50 μL of 100 μM UO2 2+ and 50 μL of 1000 μM of each metal ion), and a sample without adding metal interfering ions was prepared as a blank sample. After the prepared sample was allowed to stand for 30 minutes, it was shaken and the fluorescence emission spectrum was measured using FL-2700.
[0063] (2) Anions
[0064] Take 5 mg of TPE-COP and disperse it in 200 mL of DMAC to prepare a 0.025 mg / mL TPE-COPs stock solution. Take several 1.5 mL centrifuge tubes, add 900 μL of the stock solution, and then add 100 μL of ionic solution (50 μL of 100 μM UO2 2 + and 50 μL of 10000 μM anion) and a sample without adding anion interfering ions was prepared as a blank sample. After the prepared sample was allowed to stand for 30 minutes, it was shaken and the fluorescence emission spectrum was measured using FL-2700.
[0065] (3) Masking experiment
[0066] from Fig.10 It can be seen that Fe 3+ and Cu 2+ It will strongly interfere with the fluorescence intensity of TPE-COPs to uranyl ions, so 1 equivalent of EDTA was selected to 3+ and Cu 2+ Masking (Fe 3+ and Cu 2+ Equivalent, Fe 3+ and Cu 2+ The final concentration of each was 50 μM. Fig.11 It can be seen that EDTA can successfully mask Fe 3+ and Cu 2+ Interference of TPE-COPs on UO2 2+ Response.
[0067] 8. Quantitative analysis
[0068] In order to investigate the effect of TPE-COPs on UO2 2+ The detection sensitivity of different UO2 2+ The fluorescence spectra of TPE-COPs were tested at different concentrations.
[0069] The fluorescence intensity of TPE-COPs increases with the change of UO2 2+ The concentration of UO2 increased with the increase of 2+ The fluorescence intensity increased by 10.9 times compared with the blank. Fig.12 The fluorescence intensity of TPE-COPs at 401 nm is shown in Figure 2. 2+ The linear response curve of TPE-COPs to UO2 2+ The detection limit is 30.6nM (about 7.238ng / L), which is lower than the World Health Organization's limit on UO2 in drinking water. 2+ The contamination limit (30ng / L) proves that TPE-COPs can be used for UO22+ Highly sensitive detection.
[0070] In addition, by Figure 3 and Fig.12 The results show that the fluorescence intensity of TPE-COPs increases with the increase of uranyl ion concentration, and in the range of 0-6 μM UO2 2+ A good linear relationship is shown in the range, indicating that the covalent organic polymer TPE-COPs of the present invention belongs to a Turn-On type fluorescent polymer.
[0071] 9. Determination of actual water samples
[0072] The TPE-COPs were evaluated for the detection of UO2 in real water samples. 2+ The applicability of the TPE-COPs was investigated, and the accuracy of the measurement was verified by the spike recovery method. The volume of the water sample was 100 μL. As shown in Table 2, the use of TPE-COPs can achieve high recovery rates of uranium in Pearl River water and radium slag water samples, with recoveries of 99.7%-102.5% and 102.3%-105%, respectively, and the corresponding relative standard deviations (RSDs) were 4%-6.5% and 2.1%-4.2%, respectively. The above results show that the new TPE-COPs have good accuracy and are expected to be reliably applied to the detection of UO2 in actual water samples. 2+ Rapid on-site testing.
[0073] Table 2 UO2 in Pearl River water and radium slag water samples using TPE-COPs 2+ The results of the measurement
[0074]
[0075] *UO2 of the sample 2+ The initial concentration was determined by ICP-MS method.
[0076] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A Turn-On fluorescent polymer, characterized in that: The fluorescent polymer has the structure shown below:
2. The method for preparing the Turn-On fluorescent polymer according to claim 1, characterized in that: Mix tetraphenylethylenetetraaldehyde and 3,3-dihydroxybenzenediamine, then add 1,4-dioxane, benzyl alcohol, mesitylene and acetic acid solution, degas and seal under vacuum after fully dissolving, then let stand in a greenhouse for more than 3 days, and finally collect the yellow solid product.
3. The method for preparing a Turn-On fluorescent polymer according to claim 2, characterized in that: The molar ratio of tetraphenylethylenetetraaldehyde to 3,3-dihydroxybenzenediamine is 1:1-3.
4. The method for preparing a Turn-On fluorescent polymer according to claim 2, characterized in that: The concentration of the acetic acid solution is 5-7M.
5. The method for preparing a Turn-On fluorescent polymer according to claim 2, characterized in that: The volume ratio of the 1,4-dioxane, benzyl alcohol, mesitylene and acetic acid solution is 700-900:700-900:1315-1355:150-250.
6. Use of the Turn-On fluorescent polymer according to claim 1 in detecting uranyl ions.
7. The use according to claim 6, characterized in that: The method for detecting uranyl ions is specifically as follows: the Turn-On fluorescent polymer described in claim 1 is dispersed in a solvent to prepare a 0.01-0.05 mg / mL stock solution, and then a test solution containing uranyl ions is added to the stock solution at a volume ratio of 8-10:1, and after standing for more than 30 minutes, the fluorescence emission spectrum is measured at an excitation wavelength of 314 nm, and finally the uranyl ion concentration of the test solution is obtained according to a linear response curve between the fluorescence intensity at 401 nm and the uranyl ion concentration.
8. The use according to claim 7, characterized in that: The solvent is a mixed solvent of DMAC / H2O=9:
1.
9. The use according to claim 7, characterized in that: The stock solution also contains EDTA.
10. The use according to claim 7, characterized in that: The detection limit of uranyl ion was 30.6 nM.
Citation Information
Patent Citations
Preparation method and application of imine bond connected fluorescent covalent organic framework
CN113929905A
Preparation method of three-dimensional covalent organic framework and adsorption application of three-dimensional covalent organic framework
CN115678022A
Preparation method and application of electrochromic covalent organic framework film
CN118581473A